Identification of Intracellular and Plasma Membrane Calcium Channel Homologues in Pathogenic Parasites - Prole, David L.; Taylor, Colin W. (PLOS ONE, 2011)
Ca2+ channels regulate many crucial processes within cells and their abnormal activity can be damaging to cell survival, suggesting that they might represent attractive therapeutic targets in pathogenic organisms. Parasitic diseases such as malaria, leishmaniasis, trypanosomiasis and schistosomiasis are responsible for millions of deaths each year worldwide. The genomes of many pathogenic parasites have recently been sequenced, opening the way for rational design of targeted therapies. We analyzed genomes of pathogenic protozoan parasites as well as the genome of Schistosoma mansoni, and show the existence within them of genes encoding homologues of mammalian intracellular Ca2+ release channels: inositol 1,4,5-trisphosphate receptors (IP3Rs), ryanodine receptors (RyRs), two-pore Ca2+ channels (TPCs) and intracellular transient receptor potential (Trp) channels. The genomes of Trypanosoma, Leishmania and S. mansoni parasites encode IP3R/RyR and Trp channel homologues, and that of S. mansoni additionally encodes a TPC homologue. In contrast, apicomplexan parasites lack genes encoding IP3R/RyR homologues and possess only genes encoding TPC and Trp channel homologues (Toxoplasma gondii) or Trp channel homologues alone. The genomes of parasites also encode homologues of mammalian Ca2+ influx channels, including voltage-gated Ca2+ channels and plasma membrane Trp channels. The genome of S. mansoni also encodes Orai Ca2+ channel and STIM Ca2+ sensor homologues, suggesting that store-operated Ca2+ entry may occur in this parasite. Many anti-parasitic agents alter parasite Ca2+ homeostasis and some are known modulators of mammalian Ca2+ channels, suggesting that parasite Ca2+ channel homologues might be the targets of some current anti-parasitic drugs. Differences between human and parasite Ca2+ channels suggest that pathogen-specific targeting of these channels may be an attractive therapeutic prospect.